Políticas públicas de desenvolvimento territorial rural: uma análise da delimitação dos territórios rurais do Estado da Bahia, segundo a tipologia municipal - Cerqueira, Cristiane Aparecida de (2015)
Because of the historical economic and social inequality, especially in rural areas the State of Bahia, and public policies for rural territorial development instituted in the 2000s, the general objective of this work is \"Discuss the borderline of Bahian rural areas, from the identification municipal types\". So initially it describes the evolution and characteristics of initiatives, policies and international and national public programs for rural and regional development that inspired the planning and actions of the Bahian government. Then presents the historical context and the specificities of inducing the development policies in Bahia, talking about the recent process of institution of Rural Territories programs (TRs), Identity Territories (IT) and Citizenship Territories (CTs). In support of scientific systematization, this work has a theoretical review of the development, especially in its rural and territorial aspect, and an empirical review, which presents the main international and national scientific papers, which assessed the development through multidimensional variables and by multivariate methods. All this depended on bibliographical and documentary research. The Bahia characteristics were analyzed, whose descriptive analysis and factor analysis (FA) recorded a state with a rural profile, but with economic, social and environmental conditions short of Brazilian reality. As a reference of the largest and lowest level of Municipal Human Development (HDI) territorial respectively, the Territory South Coast and the Sisal Territory have become objects of research. In order to describe in what aspects Bahian rural areas or are not similar to each other; and check whether they are made of homogeneous municipalities, a descriptive and comparative analysis was performed, and estimate a Rural Development Index (RDI). The results show that both territories record high number of municipalities, area and resident population, aspects that hinder the historical cohesion, cultural, social and economic. Although the two territories are consistent with the requirements of TRs programs, TCs and IT, the Territory Sisal has more rural profile and economic and social conditions most critical. The IDR shows heterogeneity in the two territories, although the Territory of Sisal, focus greater number of municipalities with lower levels of rural development. With the intention of \"propose methodologies for the delimitation of rural areas\", the results point 2 or 3 types of Spatial Clusters for both the Territory South Coast and for the Territory Sisal, groups composed of surrounding municipalities and with homogeneous characteristics. Through the main crops, the effective livestock, the various activities and displacement flow from the occupied have been identified different along guide ideas of each territory. Therefore, the results reveal that the South Coast Territory and the Sisal Territory are formed by heterogeneous municipalities; and that depending on the study variable and the type of method chosen, different possibilities for subdivision are possible territories. The important thing is to identify the demographic, social, cultural, economic, environmental characteristics; identify problems, challenges, possibilities, representative identity of territorial cohesion, able to promote rural development.